Stress distribution in implant-supported prosthesis with external and internal implant-abutment connections - Goiato, Marcelo Coelho [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Falcón-Antenucci, Rosse Mary [UNESP]; Santos, Daniela Micheline dos [UNESP]; Haddad, Marcela Filié [UNESP]; Bannwart, Lisiane Cristina [UNESP]; Moreno, Amália [UNESP] (MJS Publishing, Medical Journals Sweden AB, 2013)
Objective. This study aimed to investigate the stress distribution in screwed implant-supported prostheses with different implant-abutment connections by using a photoelastic analysis. Materials and methods. Four photoelastic models were fabricated in PL-2 resin and divided according to the implant-abutment connection (external hexagon (EH) and Morse taper (MT) implants (3.75 × 11.5 mm)) and the number crowns (single and 3-unit piece). Models were positioned in a circular polariscope and 100-N axial and oblique (45) loading were applied in the occlusal surface of the crowns by using a universal testing machine. The stresses were photographically recorded and qualitatively analyzed using software (Adobe Photoshop). Results. Under axial loading, the MT implants exhibited a lower number of fringes for single-unit crowns than EH implants, whereas for a 3-unit piece the MT implants showed a higher number of fringes vs EH implants. The oblique loading increased the number of fringes for all groups. Conclusion. In conclusion, the MT implant-abutment connection reduced the amount of stress in single-unit crowns, for 3-unit piece crowns the amount of stress was lower using an external hexagon connection. The stress pattern was similar for all groups. Oblique loading promoted a higher stress concentration than axial loading. © Informa Healthcare.
Keywords: Biomechanics; Dental implants; Fixed prosthesis; Photoelastic stress analysis; Screw retained; biomechanics; dental abutment; human; theoretical model; tooth implant; Dental Implant-Abutment Design; Dental Implants; Humans; Models, Theoretical